Inflammatory damage on respiratory and nervous systems due to hRSV infection. (October 2015) - Bohmwald, Karen; Espinoza, Janyra A; Becerra, Daniela; Rivera, Katherine; Lay, Margarita K; Bueno, Susan M; Riedel, Claudia A; Kalergis, Alexis M
Highlights: We discuss about how interferons contribute at controlling viral infection. We discuss the role of IL-17 in lungs damage due to hRSV infection. We consider the involvement of the central nervous system in hRSV pathology. Abstract : The exacerbated inflammatory response elicited by human Respiratory Syncytial Virus (hRSV) in the lungs of infected patients causes a major health burden in the pediatric and elderly population. Since the discovery of hRSV, the exacerbated host immune-inflammatory response triggered by this virus has been extensively studied. In this article, we review the effects on the airways caused by immune cells and cytokines/chemokines secreted during hRSV infection. While molecules such as interferons contribute at controlling viral infection, IL-17 and others produce damage to the hRSV-infected lung. In addition to affecting the airways, hRSV infection can cause significant neurologic abnormalities in the host, such as seizures and encephalopathy. Although the origin of these symptoms remains unclear, studies from patients suffering neurological alteration suggest an involvement of the inflammatory response against hRSV.